Uso de recursos alimentares por peixes imaturos e adultos de espécies piscívoras em uma planície de inundação neotropical. - Bozza, André Nogueira (2010)
The aim of this study was to evaluate the use of food resources by juveniles and adults of Acestrorhynchus lacustris, Hemisorubim platyrhynchos, Hoplias aff malabaricus, Plagioscion squamosissimus, Pseudoplatystoma corruscans e Salminus brasiliensis from the upper Paraná River floodplain, sampled quarterly between March 2007 and December 2008. The quantitative trophic composition was obtained by prey volume (% volume) and diet niche breadth of each piscivorous species, as well as trophic relationships among them through diet niche overlap, diet similarity and prey size. The diet of the species was composed of fish-preys (42 species), crustaceans and insects, with ontogenetic diet changes, except to P. corruscans. The niche breadth was high to H. aff. malabaricus adults and low to P. corruscans adults and P. squamosissimus juveniles. The niche overlap values was generally low, with null values for P. corruscans related to other species and high intra specific values related to juveniles and adults. Diet similarity was high to Characidae species consumers and low to P. squamosissimus juveniles, which consumed mainly crustaceans. Positive correlation was found between prey and predator size, however, each piscivorous species consumed different prey sizes, presenting no correlation among them. Results showed that the six species consumed fish since juveniles, however, with low diet similarity and intra and inter specific niche overlap to most of them, and the prey size consumed increased in relation to predator size and varied among species. Thus, the piscivorous species diet depends of prey species distribution and colonization, morphology and feeding behavior of the prey as well as the predator.